Case Report: Efficiency of Embolization Microcoils for the Repair of Brachiocephalic Vein Perforation During Hemodialysis Catheter Placement - Hu, Ying; Gu, Fujia; Yuan, Ping; Shi, Min; Ma, Liang; Zha, Yan; Fu, Ping (Frontiers in Medicine, 2021)
Background: The cuff catheter is one of the most common routes of vascular access in hemodialysis patients, while severe complications can occur during cuff catheter placement, such as bleeding, hematoma, and artery or vein damage. During catheterization, brachiocephalic vein perforation associated with a mediastinal lesion is rare. Open chest repair is effective for brachiocephalic vein perforation during catheter placement, but it entails a risk of potentially lethal trauma. Interventional treatment can be considered to reduce injury in this context, but relevant reports are limited. Case report: Herein, we describe our experience with a 68-year-old male hemodialyzed patient in whom cuff catheter vascular access was required for regular hemodialysis. He complained of mild pain in the left side of his chest during cuff catheter placement. The surgeon immediately checked the location of the catheter. Digital subtraction angiography revealed that the hemodialysis cuff catheter had punctured the mediastinal area from the left brachiocephalic vein. The patient was diagnosed with left brachiocephalic vein perforation (d ≈ 5 mm). Fortunately, the brachiocephalic vein perforation was successfully repaired with two embolization microcoils after comprehensive assessment and multidisciplinary consultation. Conclusion: Brachiocephalic vein perforation can be repaired with embolization microcoils during hemodialysis catheter placement, and this method of interventional treatment is safe and effective.